Recycling and phosphorylation of eukaryotic initiation factor 2 on 60S subunits of 80S initiation complexes and polysomes. - Ramaiah, K V (1992)
Phosphorylation of the alpha-subunit (38 kDa) of eukaryotic initiation factor 2 (eIF-2 alpha) regulates initiation of protein synthesis in eukaryotic cells. This phosphorylation is enhanced in cycloheximide-treated heme-deficient reticulocyte lysates in which polysomes are maintained. In early heme deficiency prior to polysome disaggregation, eIF-2(alpha P) accumulates primarily on the 60S subunits of polysomes. Further, isolated polysomes contain eIF-2 alpha that is efficiently phosphorylated in vitro by heme-regulated inhibitor (HRI). Immunoblot analysis of eIF-2 distribution in sucrose gradients of actively protein-synthesizing lysates indicates that eIF-2 is distributed at low levels throughout the polysome profiles. These findings suggest that polysome-bound eIF-2 alpha is a target of HRI under physiological conditions. The presence of eIF-2 on the 60S subunits of polysomes is incompatible with the conventional model in which eIF-2 is recycled during the joining of the 48S preinitiation complex and the 60S subunit to form the 80S initiation complex. A modified model is presented with emphasis on the translocation of eIF-2 from the 40S ribosomal subunit of the 48S preinitiation complex (eIF-2.GTP.Met-tRNA(f).40S.mRNA) to the 60S subunit of the 80S initiation complex.